The study of home-buyers’ satisfaction towards purchasing houses in residential areas - Nurhidayah, Azmy; Nur Afiqa, Tutur (Penerbit Universiti Malaysia Pahang, 2022)
As the world evolves across cultures and centuries, people has become master builders and construct different kinds of houses for themselves and the community. Houses act as shelters and typically have basic features that protects the occupants from rain or sunlight, however, the features and functionality of houses nowadays has gone through so much improvement to cater the needs of homebuyers. Most homebuyers decides on purchasing a house based on their limited knowledge on real estate purchasing, and a lot of them did not conduct research prior to purchasing a house. This resulted in dissatisfied homebuyers and end up making them spend more money in the long term as to perform maintenance work (if they purchased low quality houses). This paper explores the satisfaction of homebuyers towards purchasing houses in residential area by validating the three contributing factors towards achieving homebuyers’ satisfaction found from the literature. This study assists in highlighting the vital aspects that developers should focus on in residential construction in order to increase the level of satisfaction of homebuyers during the post-construction phase. Three factors were identified from the literature as the factors contributing to homebuyers’ satisfaction which are (i) home warranty, (ii) suitable location with complete facilities, and (iii) security protection. A total of 55 questionnaires were distributed to homebuyers in Taman Nusa Intan, Senawang, Negeri Sembilan. Based on the Pearson Correlation Coefficient, all variables have positive correlations and indicates that the three factors do contribute towards homebuyers’ satisfaction in purchasing houses. In order to achieve homebuyers’ satisfaction, developers need to ensure that workmanship during construction is performed according to standards to avoid resulting in bad quality and hence produce defects during the handover process to the homebuyers. Defects that were identified then need to be made good during the warranty period and need to be exercised fully to benefit the homebuyers.